2000
DOI: 10.1093/neurosurgery/46.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Outcomes and Long-term Follow-up Results after Enhanced Chemotherapy Delivery for Primary Central Nervous System Lymphoma

Abstract: BBBD-enhanced chemotherapy delivery, without subsequent radiotherapy, resulted in favorable survival and cognitive outcomes for patients with primary central nervous system lymphomas who had not previously undergone irradiation. A cooperative multicenter study of intravenous chemotherapy without radiotherapy versus BBBD-enhanced chemotherapy would address the feasibility and necessity of performing a Phase III study for these rare central nervous system malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
72
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 152 publications
(74 citation statements)
references
References 22 publications
1
72
0
1
Order By: Relevance
“…Employing systemic high dose MTX alone Guha-Thakurta et al reported a 100% response rate; however, median progression free survival was 16.7 and median overall survival only 30.4 months in 31 patients 57. However, this treatment modality is invasive, requires general anaesthesia, and is associated with potential acute neurotoxicity (seizures in 6% to 8% of the procedures, strokes in 6.8% of the patients) 7.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Employing systemic high dose MTX alone Guha-Thakurta et al reported a 100% response rate; however, median progression free survival was 16.7 and median overall survival only 30.4 months in 31 patients 57. However, this treatment modality is invasive, requires general anaesthesia, and is associated with potential acute neurotoxicity (seizures in 6% to 8% of the procedures, strokes in 6.8% of the patients) 7.…”
Section: Discussionmentioning
confidence: 99%
“…In 74 patients treated with intra-arterial cyclophophamide and high dose MTX after blood-brain barrier opening a median overall survival of 40.7 months has been reported without long term neurotoxicity as documented by serial neurosychological testing in 23 out of these 74 patients with ongoing complete remission 7. However, this treatment modality is invasive, requires general anaesthesia, and is associated with potential acute neurotoxicity (seizures in 6% to 8% of the procedures, strokes in 6.8% of the patients) 7. In a combined pilot/phase II study on 14 patients treated with systemic high dose MTX, thiotepa, vincristine, dexamethasone, and intraventricular MTX and ara-C a 79% complete remission has been achieved with a median progression free survival of 16.5 months and a projected minimum median overall survival of 40 months 6…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations